1999
DOI: 10.1021/tx9901074
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Ochratoxin A by an Fe−Porphyrin System:  Model for Enzymatic Activation and DNA Cleavage

Abstract: Ochratoxin A (OTA, 1) is a fungal toxin that facilitates single-strand DNA cleavage, DNA adduction, and lipid peroxidation when metabolically activated. To model the enzymatic activation of OTA, we have employed the water-soluble iron(III) meso-tetrakis(4-sulfonatophenyl)porphyrin (FeTPPS) oxidation system. In its presence, OTA has been found to facilitate single-strand cleavage of supercoiled plasmid DNA through production of reactive oxygen species (ROS) (i.e., the hydroxyl radical, HO(*)). The reaction of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(142 citation statements)
references
References 44 publications
10
131
1
Order By: Relevance
“…A role for cytochrome P450 in this reaction was also suggested (Omar et al 1991). Other authors have reported that the OTA hydroquinone/quinone couple was generated from the oxidation of OTA (phenol oxidation) by electrochemical, photochemical and chemical processes (Gillman et al 1999, Dai et al 2002. The quinone is thought to be a likely candidate for covalent binding to DNA.…”
Section: Oxidative Stressmentioning
confidence: 93%
See 1 more Smart Citation
“…A role for cytochrome P450 in this reaction was also suggested (Omar et al 1991). Other authors have reported that the OTA hydroquinone/quinone couple was generated from the oxidation of OTA (phenol oxidation) by electrochemical, photochemical and chemical processes (Gillman et al 1999, Dai et al 2002. The quinone is thought to be a likely candidate for covalent binding to DNA.…”
Section: Oxidative Stressmentioning
confidence: 93%
“…It can also undergo reductions to form semiquinone and hydroquinone. Such events are likely to result in redox cycling and in the generation of reactive oxygen species (Gillman et al 1999, Dai et al 2002. The actual relevance of these reactions for the physiological in vivo situation has still to be elucidated.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…OTA possesses a chlorophenolic group, and chlorophenols are well known to undergo oxidative dechlorination reactions to afford quinone/ hydroquinone redox couples (15,16). The hydroquinone metabolite (OTHQ, Figure 1) of OTA has been detected in the urine (17) and kidneys (18) of rats, and in human blood and urine samples (19).…”
Section: Abstract: Bioactivation Carcinogenicity Dna Adduction Glmentioning
confidence: 99%
“…Figure 3 shows the twodimensional Table 2. The Table also includes 1 H chemical shift data for OTHQ, which was also recorded in DMSO-d 6 (16), and OTA, which was recorded in CDCl 3 by Dais et al (36). The NMR data together with the MS data provided an unambiguous assignment of the OTB-NAC structure, as 1 H signals for the attached NAC moiety could be determined and H-6 of the OTB component was observed at ~ 8 ppm, as expected from the 1 H NMR data for OTHQ (16) and OTA (36).…”
Section: Generation Of Gsh and Nac Conjugatesmentioning
confidence: 99%
“…in rats (Xiao et al, 1996a). The OTAderived quinones (OTQ/OTHQ) (figure 1) and their glutathione conjugate (OTHQ-GS) have been hypothesized as possible reactive metabolites (Dai et al, 2002;Gillman et al, 1999) and related with the genotoxic effects of OTA (Pfohl-Leszkowicz and . The presence of O-labile ester conjugates of OTA (figure 1) was also found in the urine of F344 rats after a single oral dose of OTA .…”
Section: Metabolismmentioning
confidence: 99%